MEMBUKA POTENSI PAJAK: BENTUK USAHA TETAP DARI KEGIATAN PERTAMBANGAN DI PAPUA - Faroja, Udi Hammin (Politeknik Keuangan Negara STAN, 2024)
Abundant natural resources have attracted many foreign investors to come and carry out mining and quarrying activities in Eastern Indonesia. The mining and quarrying sector is the fourth largest contributor to the Indonesian economy. Foreign Direct Investment (FDI) from this sector is recorded at around 23% of total FDI net inflows in Indonesia. This research seeks to examine the positive impact of Foreign Direct Investment (FDI) on potential tax revenues through permanent establishments (BUT) in Papua, Eastern of Indonesia, where companies conduct their economic activities. The research method used is descriptive qualitative. This research found a positive correlation between the mining and quarrying sector, foreign direct investment (FDI), and permanent establishments (BUT).